Incidental Diagnosis of Oligosymptomatic Bilateral Perirenal Erdheim–Chester Disease during Emergency Investigation for COVID-19 Infection - Juliano Cordova Vargas; Caio Cardozo; Renata Stanzione; Lucas Fiore; Felipe D'Almeida Costa; Rodrigo Fonseca Abreu; Nelson Hamerschlak; Guilherme Perini (Case Reports in Hematology)
Erdheim–Chester disease (ECD), a rare form of non-Langerhans histiocytosis, is a multisystem disorder. The case reported here refers to a 49-year-old man presenting at the emergency room with respiratory symptoms. While undergoing diagnostic tests for COVID-19 infection, tomography revealed asymptomatic bilateral perirenal tumors, while renal function remained unaltered. ECD was suggested as an incidental diagnosis and confirmed by core needle biopsy. This report provides a brief description of the clinical, laboratory, and imaging findings in this case of ECD. This diagnosis, albeit rare, should be taken into consideration in the context of incidental findings of abdominal tumors to ensure that treatment, when required, is instituted early.